2010
DOI: 10.1080/07315724.2010.10719824
|View full text |Cite
|
Sign up to set email alerts
|

Satiating Effect of a Barley Beta-Glucan–Enriched Snack

Abstract: The BB, consumed as a midmorning snack, although able to influence appetite ratings, did not modify food intake in a short time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
(46 reference statements)
3
29
0
Order By: Relevance
“…However, we did not observe a significant effect of β-glucan on short-term energy intake. In fact, our results showed consistent outcomes with other studies that examined the effects of β-glucan-enriched or supplemented products on short-term satiety [51,52,53,54], excluding a study of using 8 g of β-glucan in biscuits and juice [55]. It was reported that molecular weight and solubility of β-glucan were important factors that determine the physiologic effect [56,57].…”
Section: Discussionsupporting
confidence: 89%
“…However, we did not observe a significant effect of β-glucan on short-term energy intake. In fact, our results showed consistent outcomes with other studies that examined the effects of β-glucan-enriched or supplemented products on short-term satiety [51,52,53,54], excluding a study of using 8 g of β-glucan in biscuits and juice [55]. It was reported that molecular weight and solubility of β-glucan were important factors that determine the physiologic effect [56,57].…”
Section: Discussionsupporting
confidence: 89%
“…Almiron-Roig et al (44) considered the addition of fiber to a yogurt drink and found that it tended to be more satiating than the other foods. In another study in which fiber was added to a food, 20 healthy adolescents were selected and randomly assigned to receive a preload of barley enriched with b-glucan or control biscuits as a midmorning snack (45). A decrease in the desire to eat and an increase in fullness and satiety were experienced with the barley b-glucan-enriched biscuits compared with the control biscuits.…”
Section: Snack Foods and Satietymentioning
confidence: 99%
“…Further, unlike old-fashioned oats instant oats are cut which exposes the endosperm and affects the β-glucan, a major component of endosperm cell walls. In studies that investigated the effects of β-glucan on satiety, data on the physicochemical properties of the fiber are singularly lacking [14-18]. Thus, investigating the physicochemical properties of the fiber would help clarify the mechanisms by which β-glucan affects satiety, the amount of β-glucan that elicits an appetite response, and the processing techniques that could facilitate development of satiety-enhancing products to replace foods in the usual diet.…”
Section: Introductionmentioning
confidence: 99%